Sarcoptes Scabiei Infection in Holland Loop Rabbits - Kadek Ferdy Agastia Dwi Pratama (Jurnal Veteriner Nusantara, 2026)
Oryctolagus cuniculus or rabbit is a popular companion animal due to its friendly temperament, calm behavior, high exploratory capacity, and ability to adapt quickly to new environments. However, both household and farm management systems present risks of compromised immunity, particularly against infectious diseases caused by viruses, bacteria, fungi, and parasites. Sarcoptes scabiei is one of the most significant parasitic agents affecting rabbits, especially when immunity is weakened and environmental sanitation is poor. Infestation commonly presents with pruritus, alopecia, erythema, hyperkeratosis, and crust formation, with predilection sites including the ears, feet, and lips. Severe cases may lead to stress and death, with reported mortality rates of 15–40%. This case report describes a holland lop rabbit exhibiting pruritus, hyperkeratosis, alopecia, and crusts on the auricula sinister et dexter, as well as alopecia and erythema on the ventro-tarsal region dexter. Treatment consisted of causative, symptomatic, and supportive therapy. Ivermectin (0.4 mg/kg, SC, every 7 days) was administered as the causative treatment, diphenhydramine HCl (0.2 mg/kg, SC) as symptomatic therapy, and Viamin 34® (1 ml/kg, SC) as supportive care. All treatments were continued for 14 days. Significant clinical improvement was observed, including the resolution of alopecia, erythema, hyperkeratosis, and crusting.